Tiktok and Pandemic (Content Analysis Tiktok Utilization As Education Medium During Covid-19 Pandemic) - Tjut Afrieda Syahara; Chusnul Azizah Indahsari; Dwi Susanti (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The pandemic due to Covid-19 has been going on for more than a year. Until this article was written, various ways have been taken by the government and institutions to stop the spread of the corona virus. Social media is one of the media that is widely used to deal with and overcome the corona virus. Tiktok is an application that is used to create a campaign to the public. Tiktok as entertainment medium, now used for education purpose one of which is the World Health Organization (WHO). This research focused on how WHO used Tiktok as a medium of education during a pandemic. The method in this research is content analysis. There are 3 types of content in the TikTok @WHO account, namely Prevention Messages, knowledge about the corona virus and humanitarian messages.